2020
DOI: 10.1186/s12884-020-03436-3
|View full text |Cite
|
Sign up to set email alerts
|

Lactation challenges of resident physicians- results of a national survey

Abstract: Background There are unique challenges to parenting in residency and there is limited data to guide policy regarding lactation facilities and support for female physicians-in-training. We aimed to assess issues surrounding breast-feeding during graduate medical training for current residents or recent graduates from United States (US) residency programs. Methods A national cross-sectional survey was sent to current and recently graduated (2017 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 13 publications
3
25
0
Order By: Relevance
“…The other main recommendation identified by our resident participants was the lack of, and need for, better infrastructure at training sites for breastfeeding trainees. Other studies corroborate these findings and have advocated for expansion of acceptable resources for lactating residents, such as dedicated lactation rooms for resident physicians and protected time for lactating residents [ 23 ].…”
Section: Discussionmentioning
confidence: 61%
“…The other main recommendation identified by our resident participants was the lack of, and need for, better infrastructure at training sites for breastfeeding trainees. Other studies corroborate these findings and have advocated for expansion of acceptable resources for lactating residents, such as dedicated lactation rooms for resident physicians and protected time for lactating residents [ 23 ].…”
Section: Discussionmentioning
confidence: 61%
“…31 In our study, one in five breastfeeding parents felt that their program did not support their breastfeeding goals at all, echoing prior reports of barriers to lactation during GME training. [32][33][34] One in four breastfeeding parents reported that they never had time or space to meet their breastfeeding goals; this group showed our study's highest average PSS scores.…”
Section: Discussionmentioning
confidence: 99%
“…13 A 2020 study found that, despite 87% and 27% of residents intending to breastfeed for 6 and 12 months, respectively, only 74% and 13% met these goals. 14 The etiology of breastfeeding discontinuation among physicians is multifactorial, with the most frequently cited reasons including inadequate access to pumping rooms, insufficient workplace and coworker support, and constrained schedules. 15,16 A common recurring theme involving barriers to pumping at work is a lack of access to "dedicated lactation rooms which were clean, private and fully equipped … in accessible locations. "…”
Section: Decades Of Both Qualitative and Quantitative Data Capture Th...mentioning
confidence: 99%